Effect of different threonine to lysine (threonine/lysine) ratios on growth performance and carcass composition in growth-finishing swine - FENG Jie; XU Zi-rong (浙江大学学报. 农业与生命科学版)
Ninety-six Duroc-Landrace-Yorkshire piglets which weighed about 28kg were randomly divided into four groups to be used in studying the different ratios of threonine to lysine (0.62, 0.67, 0.72 and 0.78) on growth performance and carcass composition in growth-finishing swine. The results showed that 0.72 was the best ratio, which increased the average daily gain, carcass lean percentage and muscle weight by 4.92%, 6.47% and 11.50% (P<0.05) respectively. Feed gain ratio and weights of organs, however, were not affected.